CSF biomarkers in frontotemporal lobar degeneration: relations with clinical characteristics, apolipoprotein E genotype, and neuroimaging. Issue 2 (17th January 2006) - Pijnenburg, Y A L; Schoonenboom, S N M; Barkhof, F; Knol, D L; Mulder, C; Van Kamp, G J; Van Swieten, J C; Scheltens, P
Abstract : In order to better understand the large variation in cerebrospinal fluid (CSF) tau and amyloid-beta(1–42) (Aβ42) in frontotemporal lobar degeneration (FTLD), relations between these biomarkers and clinical parameters, neuroimaging characteristics, and apolipoprotein E (ApoE) genotype were studied in 31 patients with FTLD, including 16 patients with the frontal variant and 15 with the temporal variant. CSF tau was highest in FTLD with predominant temporal involvement. In the frontal subgroup, CSF tau level was influenced by the number of ApoE ε3 alleles. In the temporal subgroup, CSF tau level was dependent on a combination of CSF Aβ42, age, disease duration, and disease severity. No relation with degree of atrophy or asymmetry on neuroimaging could be established. CSF Aβ42 variability remained unexplained. Future research could study the role of ApoE genotype and Aβ42 in FTLD, as well as establish measures for disease intensity.